The Effect of Motivation and Learning Effectiveness and the Quality of Economic Education Study Program Graduates - Zuhri Saputra Hutabarat (STAI Hubbulwathan Duri, 2022)
This research was conducted to find out information and learning learning to the quality of study program Economic Education University of Jambi. This research uses survey method with correlational approach. The in place of this research is the study program Economic Education University of Jambi with the number of affordable population as much as 325 graduates. Data collection using questionnaire instrument. The sampling technique is done randomly with the following steps: First, calculate the target population of all Economic Education courses in Jambi University; second, the number of people reachable by lottery gives the order number; third, selecting 20 random people in statistics to try; Fourth, select 50 random people in the sample to sample the research. This research produces; (a) There are factors influencing the feasibility of Economic Education Universitas Jambi; (b) There are many things that affect the quality of graduates. The implication of this research is the effort to improve the quality that can be done by improving the motivation and study of the students of Economic Education Universitas Jambi.